Investigation of a Foodborne Outbreak at a Breaking Fast Event in Gunung Gempal Village, Kulon Progo, 2024 - Askhori, Samsul; Damayanti, Siska Yulia; Padmiyati, Eny; Indriani, Citra; Rahayujati, Theodola Baning (BKM Public Health and Community Medicine, 2024)
Purpose: This investigation aimed to confirm the existence of a foodborne outbreak, identify the causative agent, and determine contributing factors to formulate control recommendations. Methods: The investigation followed WHO guidelines for foodborne outbreak investigation. A case was defined as experiencing one or more symptoms such as diarrhea, abdominal pain, dizziness, nausea, and fever after consuming a meal box at a breaking fast event on March 30, 2024. Data were collected using Google Forms sent via WhatsApp and through direct interviews with the community. An environmental investigation was conducted by observing the catering service. Results: A total of 114 cases (attack rate = 45.6%) were identified, with primary symptoms being diarrhea (42.8%), abdominal pain (26.8%), weakness (22%), dizziness (10.8%), and nausea (9.6%). The epidemic curve indicated a typical source pattern. Most cases were female (64%) and aged 19-59 (51.7%). The average incubation period was 9.5 hours (1-17 hours). Grilled chicken had the highest attack ratio of 2.7. Interviews revealed that 41% of cases reported the grilled chicken had an unpleasant odor, 25% reported an unusual taste, and 12% reported a mushy texture. Based on the incubation period, symptoms, and implicated food, Staphylococcus aureus was suspected as the causative agent. The processing of grilled chicken took 34 hours until consumption. Risk factors were inadequate food handling, high-temperature storage, long preparation time, and poor sanitation. No food, vomit, or stool samples were available for laboratory testing. Conclusion: A foodborne outbreak occurred following a breaking-fast event in Gunung Gempal Village. Consuming grilled chicken was a contributing factor. Training on food safety for catering services is recommended.